Etika Pendidikan Islam Dalam Konteks Modern - Chanfiudin Chanfiudin; Lukman Lukman; Robby Setiawan; Indra Wahyu Saputra (STIKes Ibnu Sina Ajibarang, 2024)
Islamic Education Ethics in the Modern Context is a study that explores the relevance of Islamic ethical values ​​in the context of contemporary times. In the era of globalization and technological progress, the challenge faced by Islamic education is how to combine traditional principles with the demands of the modern era. This article highlights the importance of understanding and applying Islamic teachings in education contextually and relevant to the times, without losing the substance of the underlying ethical values. This discussion also includes strategies for integrating Islamic ethics in educational curricula, teacher training, and the overall educational environment. Thus, this article aims to provide insight into how Islamic education can remain a moral foundation in facing the dynamics of the modern era.